Will prevention be better than cure? The challenge of retaining health staff in the public health sector in Sri Lanka - P. K. Buddhika Mahesh; M. Wasantha Gunathunga; S. Mahendra Arnold; L. Sinha D. de Silva; Monika P. Wijeratne; Janaka Weragoda (College of Community Physicians of Sri Lanka, 2018)
No abstract available